KNOWLEDGE STRUCTURE OF SUSTAINABLE COMMUNITY BASED TOURISM: A BIBLIOMETRIC AND NETWORK ANALYSIS - Mansyur, Abdurrahman; Hadi, Firno (Jurnal Pariwisata Indonesia, 2025)
This study maps the knowledge structure of Sustainable Community Based Tourism (SCBT) through a bibliometric and network analysis using data extracted from the Scopus database on 14 October 2025. The search string “Sustainability” AND “Community Based Tourism” was applied to identify relevant publications. Biblioshiny (R-Studio) was employed to examine publication trends, collaborative networks, and thematic structures within the field. The findings reveal a steady expansion of SCBT research, particularly after 2015, with strong contributions from Asia and increasing interdisciplinary integration. Co authorship and institutional network analyses indicate growing collaboration, though geographical imbalances remain evident. Keyword cluster mapping highlights dominant themes such as community participation, environmental conservation, governance, and digital transformation. The analysis also exposes persistent gaps, including limited cross regional perspectives and insufficient integration of sustainability, technology, and community empowerment into unified frameworks. This study offers a structured overview of the intellectual landscape of SCBT and provides recommendations to guide future research directions.